Efficient N-arylation of 4-chloroquinazolines en route to novel 4-anilinoquinazolines as potential anticancer agents - Nishimura, Rodolfo H. V.; dos Santos, Thiago; Murie, Valter E.; Furtado, Luciana C.; Costa-Lotufo, Leticia V.; Clososki, Giuliano C. (Beilstein Journal of Organic Chemistry, 2021)
Microwave-mediated N-arylation of 4-chloroquinazolines in THF/H2O rapidly and efficiently afforded a library of novel 6-halo-2-phenyl-substituted 4-anilinoquinazolines. The methodology was compatible with numerous ortho-, meta-, and para-substituted N-methylanilines as well as substituted anilines and furnished the corresponding 4-anilinoquinazolines in good yields. Preliminary screening of the synthesized compounds against tumor cells (HCT-116 and T98G) showed promising antiproliferative properties.
Keywords: 4-anilinoquinazoline; anticancer agents; N-arylation; 4-chloroquinazoline; microwave irradiation